2012
DOI: 10.1021/ja3067622
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable N2-Intercalated WO3 Photoanodes for Water Oxidation

Abstract: Synthesis of AmmoniumIn a 20-ml vial, 1.00 g (4.00 mmol) of tungstic acid (Alfa Aesar 82118) was suspended in 5.0 ml water at 80 °C under rigorous stirring. After dropwise addition of 3.00 ml (9.9 mmol) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(146 citation statements)
references
References 48 publications
7
139
0
Order By: Relevance
“…Therefore we also examined the modifications of the absorption spectrum of the oxide upon insertion of N 2 , although for computational convenience we considered a concentration higher than in experiments ( We carried out calculations of N 2 in SC WO 3 , with a di-nitrogen concentration of 1N 2 :1WO 3 . The latter is higher than reported experimentally [9] and was chosen for computational convenience, and because we were interested in probing a qualitative effect of N 2 intercalation in WO 3 ). The computed GW-BSE spectrum of N 2 @WO 3 in Fig.…”
Section: Optical Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore we also examined the modifications of the absorption spectrum of the oxide upon insertion of N 2 , although for computational convenience we considered a concentration higher than in experiments ( We carried out calculations of N 2 in SC WO 3 , with a di-nitrogen concentration of 1N 2 :1WO 3 . The latter is higher than reported experimentally [9] and was chosen for computational convenience, and because we were interested in probing a qualitative effect of N 2 intercalation in WO 3 ). The computed GW-BSE spectrum of N 2 @WO 3 in Fig.…”
Section: Optical Spectramentioning
confidence: 99%
“…However its optical gap (3.0 eV [7]) is larger than desired to absorb visible light. Tungsten trioxide (WO 3 ) is another promising oxide for use in photo-electrochemical water-splitting systems [8][9][10][11][12]: it is stable against photocorrosion; its optical gap (2.6-2.7 eV) is smaller than that of TiO 2 and it may absorb sufficient visible light to generate modest photocurrents. Furthermore WO 3 electrochromism has additional applications, in e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13] A recent report showed that a thin tungsten oxide overlayer with dual oxygen and tungsten vacancies on mesoporous WO3 photoanodes improved photocurrents by a factor of 2.4 due to better interfacial charge transfer and conductivity. [14] Tungsten oxide has been extensively studied theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…The goal here entailed adding a dopant into the WO3 lattice with the aim of modifying electronic energy levels via intercalation stress which lowered the 2.6 eV band gap of WO3 to 1.9 eV to improve solar light collection efficiency [1]. As high temperature can cause the loss of intercalated dopants via thermal migration out of the unit cell, we sought to examine the possibility of using an alternative method to dope semiconductors to stimulate intercalation and/or chemical reaction with WO3 that does not add heat : useful hard x-ray photochemistry [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%